Administration of medicines by emergency nurse practitioners according to protocols in an accident and emergency department. Issue 4 (July 1997) - Marshall, J; Edwards, C; Lambert, M
Abstract : OBJECTIVE: To present the legal and professional issues related to nurse administration of drugs according to protocols, and describe the implementation and initial audit findings of such a scheme. SETTING: Accident and emergency (A&E) department of a district general hospital. METHODS: Analysis of legal and professional opinion. Protocols acceptable to the medical, nursing, and pharmacy professions were developed across a wide range of drugs appropriate for administration by accident and emergency nurse practitioners (ENPs). The first six months of the scheme were audited. Audit initially addressed general compliance with protocols and later the specific areas of tetanus immunisation and emergency contraception. RESULTS: ENPs assessed 2925 patients in six months (10.9% of all new patients); 455 patients (15.5% of the ENP patients) were given drugs according to protocols. There were no breaches of the protocols. Subsequent audit of tetanus immunisation showed 94-100% compliance with protocol standards and 71-100% compliance for emergency contraception. CONCLUSIONS: There are no legal or professional obstacles to the development of protocols for the administration of drugs to patients by nurses without reference to a doctor, providing the protocols meet all the requirements of the UKCC and have the support of consultant medical staff. Such a system must be subject to regular audit to promote a dynamic approach to protocols and training. The system safely enhanced the quality of care of patients treated by ENPs in A&E.